PENGARUH PELATIHAN DAN KOMPETENSI TERHADAP PRESTASI KERJA PADA BADAN ASET DAN PENDAPATAN DAERAH KABUPATEN PASAMAN BARAT - Endang Tirtana Putra (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2017)
This research is intended to see how the impact of Training and Competence on Job Performance at the Regional Assets and Income of Pasaman Barat Regency. Population and sample in this research is all employees of Agency of Asset and Revenue of Regency of Pasaman Barat with number 77 peoples. Sampling technique using total sampling technique. From the results of this study got the variables Training (X1) and Competence (X2) have a significant effect on Job Performance (Y) with a significant level of 0.000. The magnitude of the effect of Training (X1) and Competence (X2) on Job Performance (Y) is 0.641 (R2 = 64.1).